Long-Term renal function after implantation of continuous-flow left ventricular assist devices: A single center study. (December 2021) - Bujo, Chie; Amiya, Eisuke; Hatano, Masaru; Ishida, Junichi; Tsuji, Masaki; Kakuda, Nobutaka; Narita, Koichi; Saito, Akihito; Yagi, Hiroki; Ando, Masahiko; Shimada, Shogo; Kimura, Mitsutoshi; et al.
Abstract: Background: Implantable continuous-flow left ventricular assist device (LVAD) improve renal function in advanced heart failure. However, the long-term effects of LVAD on renal function have not been investigated thoroughly. We aimed to assess long-term renal function in patients with LVAD support and to identify predictors for late deterioration in renal function (LDRF). Methods: One hundred patients underwent LVAD implantation as a bridge to transplant at the University of Tokyo Hospital between May 2011 and December 2018. We assessed renal function at intervals (preoperative, 1, 6, 12, 18, 24 and 30 months after LVAD implantation). We divided patients into two groups: "with LDRF, " whose renal function at 30 months had decreased by >25% compared with preoperatively (n = 14), and "without LDRF" (n = 55). Results: Renal function improved at 1 month, returned to preoperative levels at 6 months, and remained there up to 30 months after LVAD implantation. However, renal function impairment became evident in patients with LDRF 18 months after LVAD implantation. A ratio of right atrial pressure/pulmonary artery wedge pressure > 0.57 and left ventricular dimension diastole ≤ 67 mm were preoperative independent risk factors for LDRF. In addition, the incidence of perioperative acute kidney injury, ventricular arrhythmia, aortic insufficiency, and late right ventricular failure was significantly higher in patients with LDRF. Conclusion: LDRF after LVAD implantation corresponded to several risk factors, including a small left ventricle and LVAD-related complications, such as right ventricular failure.